Analysis Of Efficiency Level In Indonesian Banking Companies Listed On The Indonesian Stock Exchange For The 2019-2022 Period - Gilbert Wijaya; Rudolf Lumbantobing; Lambok D. R. Tampubolon (Green Publisher Indonesia, 2024)
This study analyzes the efficiency levels of Indonesian banking companies listed on the Indonesian Stock Exchange (IDX) during the period of 2019-2022, encompassing the impact of the Covid-19 pandemic. Efficiency in banking is crucial for maintaining competitive advantage and ensuring financial stability, especially in the face of global challenges such as economic globalization and digitalization. The research evaluates the efficiency of banks using indicators like the CAMEL method, BOPO, NIM, NPL, LDR, and CAR ratios. The study finds that the pandemic significantly affected banks' efficiency, with notable declines in NIM and ROA ratios due to economic uncertainty and operational cost challenges. Post-pandemic, these ratios have shown signs of stabilization. The study uses descriptive quantitative methods, analyzing secondary data from annual financial reports of eight banking companies listed on IDX. The results indicate that strategic measures in risk management and cost efficiency are imperative for banks to navigate future uncertainties.